Agility and supply chain uncertainty: a scenario planning perspective. (13th November 2008) - Dani, Samir; Ranganathan, Rajesh
This paper provides an insight into developing a proactive approach to predict risks and manage uncertainties that may potentially disrupt the supply chain. This paper considers the concepts of agility and scenario planning for managing risks proactively. A conceptual model has been presented which brings together the two concepts in a process model for identifying and managing supply chain risks. The model is further described by applying it to a case depicting supply chain disruption.